PERTANGGUNG JAWABAN PERUSAHAAN TERHADAP PEKERJA YANG DIRUMAHKAN (WFH) BERDASARKAN UNDANG-UNDANG NO.13 TAHUN 2003 - Arifuddin Muda Harahap; Fahri Fahrozi; Niki Marjuki; M. Harmansyah Hsb; Selmaria Purba; Indah Maya Sari Ritonga; Elza Armaini; Vita Aliyana WS; Sri Atmadianti; Twina Resia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2023)
Analyzing the company's obligation to the laid-off employees is the goal of this study. In this study, concepts, pertinent instances, and a normative approach based on legal theory were used. With data presented as narratives and conclusions drawn based on the analysis's findings, this study used a qualitative writing technique. The study's findings led to changes in a few employment laws, including Law No. 13 of 2003, which replaced it as the primary employment law. This change prevented the term